Training and coaching of public speaking skills for elementary school children in Makassar City - Arni Arni; Muhammad Yahya; Wardah Wardah; Sabriani Sabriani; Fitria Yasin; Rezki Astuti; Sofi Nur Azizah; Hasmayanti Hasmayanti (Universitas Muhammadiyah Magelang, 2023)
Children residing on Jalan Mirah Seruni, RT 05 RW 03, Pandang District, Panakukkang Village lack a foundation for effective communication. Insufficient communication skills impact their interactions with peers and parents, as well as their overall self-confidence. The objective of this community service is to enhance public speaking, communication skills, and boost self-confidence among these children. The PKM implementation method encompasses four stages: 1) preparation, 2) training, 3) mentoring and coaching, and 4) monitoring and evaluation. The outcomes of this program include heightened knowledge, improved public speaking and communication skills, leading to increased self-confidence and enthusiasm for public appearances.